Clinical outcome prediction after thrombectomy of proximal middle cerebral artery occlusions by the appearance of lenticulostriate arteries on magnetic resonance angiography: A retrospective analysis. Issue 11 (November 2018) - Kaesmacher, Johannes; Kreiser, Kornelia; Manning, Nathan W; Gersing, Alexandra S; Wunderlich, Silke; Zimmer, Claus; Kleine, Justus F; Wiestler, Benedikt; Boeckh-Behrens, Tobias
Post-ischemic vasodynamic changes in infarcted brain parenchyma are common and range from hypo- to hyperperfusion. In the present study, appearance of the lenticulostriate arteries (LSAs) on postinterventional 3T time-of-flight (TOF)-MRA suggestive for altered post-stroke vasodynamics following thrombectomy was investigated. Patients who underwent thrombectomy for a proximal MCA occlusion and for whom postinterventional 3T TOF-MRA (median at day 3) was available, were included in this retrospective analysis (n=98). LSA appearance was categorized into presence (LSA-sign + ) or absence (LSA-sign − ) of vasodilatation in the ischemic hemisphere. Functional outcome was determined using the modified Rankin scale (mRS). LSA-sign + was observed in 64/98 patients. Hypertension (adjusted OR: 0.171, 95% CI: 0.046–0.645) and preinterventional IV rtPA (adjusted OR: 0.265, 95% CI: 0.088–0.798) were associated with absence of the LSA-sign + . In multivariate logistic regression, LSA-sign + was associated with substantial neurologic improvement (adjusted OR: 10.18, 95% CI: 2.69–38.57) and good functional outcome (discharge-mRS ≤ 2, adjusted OR: 7.127, 95% CI: 1.913–26.551 and day 90 mRS ≤ 2, adjusted OR: 3.786, 95% CI: 1.026–13.973) after correcting for relevant confounders. For all clinical endpoints, model fit improved when including the LSA-sign term (p<0.05). Asymmetrical dilatation of LSAs following successful thrombectomy indicates favorable neurologic and mid-term functional outcomes. This may indicate preserved cerebral blood flow regulatory mechanisms.